Pattern of Coronary Artery Disease in Young Patients on Coronary Angiography (Medical Forum Monthly, 2021)
Objective: To find the frequency of pattern of coronary artery disease on coronary angiography in young patients of age <35years presenting with the acute coronary syndrome.Study Design: Cross-Sectional StudyPlace and Duration of Study: This study was conducted at the Angiography Ward, Punjab Institute of Cardiology, Lahore for 6 months i.e. October 2018 and November 2019.Materials and Methods: On coronary angiography, main coronary vessels were viewed and a level of stenosis was noted. The collected data was entered and analyzed by using SPSS version 20.Results: A total of 365 cases presenting with ACS who underwent coronary angiography were included in the study. The Mean age of patients was 26.68±4.04 years. After investigation 288(78.9%) patients had CAD. Among male patients, SVD was predominant followed by DVD and TVD. i.e. [SVD: 82(32.4%), DVD (26.1%) & TVD: 56(22.1%)]. Among STEMI patients, 22(17.5%) patients had normal vessels, 43(34.1%) had SVD, 31(24.6%) patients had DVD and 30(23.8%) patients had TVD. Among NSTEMI patients, 29(24.0%) patients had normal vessels, 34(28.1%) had SVD, 33(27.3%) patients had DVD and 25(20.7%) patients had TVD. However, the p-value showed no statistically significant difference for coronary artery disease in all ACS groups.Conclusion: CAD is involved in many cases at least a single vessel disease was present in maximum cases